Globalization, growth and poverty : building a inclusive world economy - Collier, Paul.; World Bank. (Oxford : Oxford University Press, 2002)
Globalization is a powerful force for poverty reduction as societies and economies around the world are becoming more integrated. Although this international integration presents tremendous opportunities for developing countries, it also has raised concerns about rising inequality, shifting power, and cultural uniformity. This report assesses the impact of globalization and addresses the ensuing anxieties. It proposes an agenda for action aimed at mitigating the risks that globalization potentially generates, while maximizing the opportunities for the poor.--Publisher description.
Foreword, Report Team, and Overview -- Chapter 1 The New Wave of Globalization and Its Economic Effects -- Chapter 2 Improving the International Architecture for Integration -- Chapter 3 Strengthening Domestic Institutions and Policies -- Chapter 4 Power, Culture, and the Environment -- Chapter 5 An Agenda for Action -- Bibliography.
Includes bibliographical references (p.161-174).
Mode of access: World Wide Web.
Keywords: Poor -- Developing countries; Economic development; Poverty -- Developing countries; Globalization -- Economic aspects; International economic integration; Developing countries -- Economic policy